PENGARUH EVALUASI FORMATIF POP TEST TERHADAP PENGUASAAN HURUF HIRAGANA - Irawan, Atria Ramadhanty (2014)
This research is motivated by the ability of students to master Hiragana letters were deemed less. Students can easily understand the Japanese's sentence patterns and vocabulary, but because Hiragana letters are different from Roman letters, it makes students feel little bit hard to master it. Although students have been studying Hiragana letters during the first semester, but students need a new way so that they can continue to be motivated to learn and master the Hiragana letters in the second semester.　Researchers provide alternative solutions using formative evaluation pop test at tenth graders of SMAN 5 Cimahi. The purpose of this study was to determine whether there are influence or not of pop test conducted on students' mastery of Hiragana characters. This study used an experimental method pure "Randomized Pretest-Posttest Control Group". The population in this study were all students of class X SMAN 5 Cimahi and the sample was 36 students of class X-2 as an experimental class and 36 students of class X-3 as a control class. Instrument in this study was a test and questionnaire.　From the analysis of the test data obtained t value= 8.08 and db = 53 then the t- table = 2.65 (5%). Based on the results of the processing of the data obtained, it was concluded t (8.08)> t table (2.65) which means that the working hypothesis is accepted while the null hypothesis is rejected. This means that there are significant differences between the experimental class and the control class, then the holding of formative evaluation test pop influence on students' mastery of Hiragana characters. This is reinforced by the results of the questionnaire. Most of the respondents replied that the holding of a pop test may increase the motivation to master Hiragana letters.